NILAI-NILAI SIMBOLIK UPACARA ADAT BELIAN MASYARAKAT DAYAK PASER KALIMANTAN TIMUR - , SOPAN T. R. MATONDANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis discusses the Belian traditional ceremony performed by the Dayak Paser located in East Kalimantan. This thesis aims to address three issues. First, to find out which is the traditional ceremony Belian. Second, to determine the values contained symbolic ceremonial Belian. Third, to determine how the development of traditional ceremonies Belian seen from the stage of cultural development. This study is a library and field research. Materials for the study of data derived from the literature associated with traditional ceremonies and interviews with several speakers from the community Paser. This study uses a material object Belian traditional ceremonies and formal object of the symbols, values, and cultural development of the theory of van Peursen. Step-by- step method used in the analysis is descriptive, internal koheresi, holistika and reflection. The results in this study are as follows. First, the ceremony is a ceremony Belian traditional medicine to cure disease caused by the supernatural. Second, Belian ceremony also contain symbols contained in clothing, offerings and implementation stages. The traditional ceremony Belian contain cultural values such as moral values, religious values, aesthetic value and social value that will affect people's lives Paser. Third, in terms of stage of cultural development. The traditional ceremony is divided into three phases. First, the mythic stage Belian traditional ceremonies still be simple and still based on the forces of nature. Both the ontological stage has been influenced by the inclusion of religion into the public Paser and third on the functional stage Belian ceremony has been influenced by developments in science and technology.